The Economic and Financial context of Well-being: An Integrated Explanation of the Social Capital - RAFFAR , ABDELKADER EL AMIR (Social Empowerment Journal, 2022)
The concept of social capital goes back to Bourdieu’s definition, which placed the focus on the existence of ‘‘network(s) of more or less institutionalized relationships … which provides each of its members with the backing of collectively-owned capital’’. The purpose of this paper is to investigate the impact of social capital on the link between financial and economic wellbeing and life satisfaction among employees within institutions. The main aim is to analyze the relationship between the various dimensions of social capital and subjective financial and economic wellbeing. this article discusses: What is social capital and how does it impact on the financial and economic well-being? For this extant literature related to the topic from different databases, websites and other available sources were collected. To answer the research questions, a literature review was conducted. The articles were selected from evidence-based scientific databases such as Emerald, Sage Premier, ScienceDirect, Springer Open, and Google Scholar. we searched relevant literature using specific keywords, e.g., “Social Capital,” “Subjective Well-Being,” “Life Satisfaction,”. Twenty-eight scholarly articles were selected by using exclusion and inclusion criteria and screening the relevant articles.